2013
DOI: 10.1074/jbc.m112.446161
|View full text |Cite
|
Sign up to set email alerts
|

Sarco(endo)plasmic Reticulum Calcium ATPase (SERCA) Inhibition by Sarcolipin Is Encoded in Its Luminal Tail

Abstract: Background: Sarcolipin is a regulator of SERCA in skeletal and atrial muscle with inhibitory properties thought to be similar to phospholamban. Results: Residues critical for SERCA inhibition reside in the luminal extension of sarcolipin. Conclusion:The luminal extension of sarcolipin is a distinct and transferrable domain that encodes most of its inhibitory properties. Significance: Sarcolipin and phospholamban use different inhibitory mechanisms to regulate SERCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
106
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(118 citation statements)
references
References 61 publications
11
106
1
Order By: Relevance
“…There is a high degree of sequence homology in the transmembrane regions of PLN and SLN, suggesting a similar mode of interaction with SERCA (6,7). Although studies have demonstrated that PLN and SLN use distinct structural elements and mechanisms to regulate SERCA (8,9), crystal structures of the SERCA-SLN (10,11) and SERCA-PLN (12) complexes are remarkably similar to one another.…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…There is a high degree of sequence homology in the transmembrane regions of PLN and SLN, suggesting a similar mode of interaction with SERCA (6,7). Although studies have demonstrated that PLN and SLN use distinct structural elements and mechanisms to regulate SERCA (8,9), crystal structures of the SERCA-SLN (10,11) and SERCA-PLN (12) complexes are remarkably similar to one another.…”
mentioning
confidence: 84%
“…For the final fit, the remaining rate constants (typically 2-4 rate constants) were allowed to vary to minimize the discrepancy between the experimental data and the kinetic model. The starting points for the kinetic simulations included global fits previously reported for the following: (i) SERCA alone (38), (ii) SERCA in the presence of wild-type PLN (21,36), and (iii) SERCA in the presence of wild-type SLN (8). Errors were calculated as the standard error of the mean based on standard deviations calculated by Dynafit.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations